Medicinal plants: how much longer? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The South African Institute for Natural Resources recently published some amazing figures about the market for medicinal plants which now reaches 27 million people, and is valued at ZAR 500 million (more than 77 million). In KwaZulu Natal alone,...